"We forgive": A group's act of forgiveness and its restorative effects on members' feelings of justice and sentiments towards the offender group. (September 2015) - Wenzel, Michael; Okimoto, Tyler G.
Although typically conceptualized as a reconciliation outcome, we propose that intergroup forgiveness can also be construed as a decision or course of action that advances justice and positive intergroup sentiments among members of the victimized group. However, the process through which this occurs depends on the perceived differentiation between the groups. Following intergroup transgressions staged in the laboratory (Study 1) or reported in news article scenarios (Study 2), participants whose victimized ingroup expressed forgiveness perceived less injustice than those whose group did not forgive, which indirectly improved intergroup sentiments. Among high ingroup identifiers and in victim groups with low relative status (i.e., more salient intergroup boundaries), forgiveness diminished feelings of injustice by reducing the perceived threat to the ingroup's status/power. In contrast, among low ingroup identifiers and in groups with high relative status, forgiveness diminished feelings of injustice by reducing the perceived threat to collectively shared values.